(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
The article examines the main stages of the development of English Romanticism, the creative peculiarities of the representatives of the “Lake School” of poets, and the contribution of George Gordon Byron to the formation of the image of the Romantic hero. The key ideas, aesthetic principles, and philosophical motifs that determined the originality of English Romantic literature at the beginning of the nineteenth century are analyzed.